FACTORS CAUSING IMPULSE BUYING IN E-COMMERCE IN WEST JAKARTA - Hartati, Monica; Rodhiah, Rodhiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
In this digital era, most of life and daily activities are related to digital and technology. Many discoveries and innovations in the utilization of digital technology continue to emerge. One of them is the emergence of e-commerce, which can facilitate and help people shop and fulfill their daily needs. Likewise, the fashion world continues to develop rapidly, both in terms of clothing models, innovations, and new local fashion brands that continue to emerge and develop. This study aims to determine the effect of fashion involvement, shopping lifestyle, sales promotion, and mobile marketing on impulse buying. The population of this study is Gen Z, who have an age range of 11–30 years and use the Shopee application in West Jakarta. This study used a sample of 213 respondents. Sample collection techniques using nonprobability sample techniques. The data collection method was obtained by distributing questionnaires online via Google Forms. The data was analyzed using SEM (structural equation modeling) through the SmartPLS3 application. The results of this study indicate that fashion involvement, shopping lifestyle, sales promotion, and mobile marketing have a positive and significant effect on impulse buying. The results of this study can provide information to Shopee and fashion brand owners about how to increase fashion involvement, shopping lifestyle, sales promotion, and mobile marketing because this can increase impulse buying. Keywords: Fashion involvement, Shopping lifestyle, Sales promotion, Mobile marketing, impulse buying